2014
DOI: 10.2174/1871527313666140612114838
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-Like and Anxiolytic-Like Effects of Cannabidiol: A Chemical Compound of Cannabis sativa

Abstract: Anxiety and depression are pathologies that affect human beings in many aspects of life, including social life, productivity and health. Cannabidiol (CBD) is a constituent non-psychotomimetic of Cannabis sativa with great psychiatric potential, including uses as an antidepressant-like and anxiolytic-like compound. The aim of this study is to review studies of animal models using CBD as an anxiolytic-like and antidepressant-like compound. Studies involving animal models, performing a variety of experiments on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(56 citation statements)
references
References 60 publications
1
54
0
1
Order By: Relevance
“…Chronic pain is an “expensive” condition, both economically and socially, yet existing pharmacotherapeutic interventions are not always adequate 3436. Taken with preclinical data on the role of the endocannabinoid system in stress, pain processing and immune homeostasis, it is clear that future investigation is warranted using controlled trials with human subjects to better understand the role that cannabis may play in treating pain, anxiety, depression and other conditions 3746…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain is an “expensive” condition, both economically and socially, yet existing pharmacotherapeutic interventions are not always adequate 3436. Taken with preclinical data on the role of the endocannabinoid system in stress, pain processing and immune homeostasis, it is clear that future investigation is warranted using controlled trials with human subjects to better understand the role that cannabis may play in treating pain, anxiety, depression and other conditions 3746…”
Section: Discussionmentioning
confidence: 99%
“…[34] In addition to these efforts, a call has been made proposing therapeutic trials of cannabidiol, which has been hypothesized to improve inflammatory-mediated symptoms in a number of chronic medical conditions. [3235] In this context, a group of researchers have suggested that Cannabidiol, a phytocannabinoid compound derived from Cannabis sativa ,[32] may offer multiple beneficial properties in humans including anti-inflammatory, anti-anxiety, antinociceptive, and anticonvulsant actions in addition to treating insomnia. [35] However, it has been emphasized that a properly designed and conducted clinical trial must be performed first to determine the efficacy and safety of the proposed cannabidiol treatment.…”
Section: Research and Therapeuticsmentioning
confidence: 99%
“…[3235] In this context, a group of researchers have suggested that Cannabidiol, a phytocannabinoid compound derived from Cannabis sativa ,[32] may offer multiple beneficial properties in humans including anti-inflammatory, anti-anxiety, antinociceptive, and anticonvulsant actions in addition to treating insomnia. [35] However, it has been emphasized that a properly designed and conducted clinical trial must be performed first to determine the efficacy and safety of the proposed cannabidiol treatment. [32] Finally, the development of a highly effective vaccine against EBOV brings the hope of long-term sustainable containment of this deadly virus.…”
Section: Research and Therapeuticsmentioning
confidence: 99%
“…CBD has broad therapeutic properties across a range of neuropsychiatric disorders, stemming from diverse central nervous system actions [11,12]. In recent years, CBD has attracted increasing interest as a potential anxiolytic treatment [13][14][15]. The purpose of this review is to assess evidence from current preclinical, clinical, and epidemiological studies pertaining to the potential risks and benefits of CBD as a treatment for anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%